2009
DOI: 10.1590/s0101-20612009000200026
|View full text |Cite
|
Sign up to set email alerts
|

Almond and peanut flours suppelmented with iron as potential ingredients to develop gluten-free cookies

Abstract: Almond and peanut flours suppelmented with iron as potential ingredients to develop gluten-free cookies Farinhas de amêndoa e amendoim suplementadas com ferro como ingredientes potenciais para desenvolvimento de biscoitos sem glútenDaniel GRANATO* 1 , Luciana de Souza Neves ELLENDERSEN 2 IntroductionCookie production has occurred since the Rock Age and its formulations and processing have been perfected continuously (PARRA, 2003). In accordance with Brasil (2005), cookies are produced by kneading and baking do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 25 publications
(24 reference statements)
2
5
0
2
Order By: Relevance
“…Flours derived from fruits, leaves, grains, tubers, and vegetables (Granato & Ellendersen, 2009) can be used as alternatives to replace wheat flour, including buckwheat flour and millet flour. Buckwheat (Fagopyrum esculentum) is a pseudocereal that presents proteins of high biological value, as well as fibers, minerals, and flavonoids (Pomeranz, 1988;Okeda & Yamashita, 1994;Abdel-Aal & Wood, 2005;Choi & Ma, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Flours derived from fruits, leaves, grains, tubers, and vegetables (Granato & Ellendersen, 2009) can be used as alternatives to replace wheat flour, including buckwheat flour and millet flour. Buckwheat (Fagopyrum esculentum) is a pseudocereal that presents proteins of high biological value, as well as fibers, minerals, and flavonoids (Pomeranz, 1988;Okeda & Yamashita, 1994;Abdel-Aal & Wood, 2005;Choi & Ma, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…One of the examples often quoted within the functional food sector is the introduction of margarine spreads fortified with plant sterols (Henry ). Among other functional foods, bakery products were also investigated as gluten‐free options: almond‐ and peanut‐flour‐based cookies fortified with iron (Granato and Ellendersen ); raw and popped amaranth‐flour‐based breads and cookies rich in protein (de la Barca and others ); protein and crude fibers enriched biscuits based on plantain and chickpeas flours (Yadav and others ). However, research in Europe has shown that there is a confusion among consumers about functional foods and they need to be informed to understand the exact benefits of such food in order to purchase it (Blades ; Annunziata and Vecchio ).…”
Section: Introductionmentioning
confidence: 99%
“…Thermogravimetric analysis (TGA) has also been used to study food composition under different thermal treatments (Fuentes and others ). Finally, numerous studies have applied multivariate analysis techniques in order to characterize different vegetable oils and nuts according to the cultivar (López and others ; Granato and Ellendersen ; Oddone and others ). The application of linear discriminant analysis (LDA) in the evaluation of traceability of extra virgin olive oil from different Italian regions, cultivars, and Mediterranean areas has been recently confirmed as suitable to determination of the providence of olive oils samples (Chiavaro and others ).…”
Section: Introductionmentioning
confidence: 99%